FRANCHISING AS A BUSINESS CONCEPT - CHANCE FOR MANY IN SERBIA - Jašarević, Alija; Ličina, Mile (Economics of Agriculture, 2013)
The development of the franchise network as an alternative solution in comparison with the traditional opening of the organizational units allows our own expansion through enganging less money and risk-sharing with local entrepreneurs who are already well familiar with its own market and its potential and had it completely checked before investing their own funds in buying a franchise. Company "Soko Stark" in Belgrade is one of the largest companies in the confectionery industry, in the region and for more than 90 years has been a leader in the domestic market. Given the fact that the concept of franchising as a business in the last decade, has been rapidly growing in all world markets, management of Soko Stark reviewed all the advantages and disadvantages of such business concept and took all necessary actions and measures as soon as possible to come out with a new strategy of development, before creating its retail network through the system of franchising. The company with its operating has its business concept proved successful so far. In the near future it plans to expand and increase the franchise system. The company has proven that it is more successful than the competition, in the confectionery market, where until recently dominated almost no one. Therefore, we expect that we could easily extend our franchise system both within our borders and in other markets as well as on the territory of the former republics.